E-Commerce in Healthcare Supply Chain: A Pathway towards Affordable, Accountable & Available Healthcare Services - Kumar, Sanjay; Kumar, Rajesh; Mittal, Amit (International Journal of Psychosocial Rehabilitation, 2019)
Standardization and integration of the healthcare supply chain are a must to explore and execute substitute ways of preventive and critical care, reaching them through non-conventional methods and improving its performance. Use of e-commerce in healthcare supply chain leads to partner relationships, information sharing, and supply chain integration. Supply chain integration has the highest standardized total effect on supply chain performance, improving the flow of information, material, and funds. This study reviews how the implementation of e-commerce in the healthcare supply chain has made healthcare services affordable, accountable, and available for all.